Visual-based intelligent solar tracking system - Abdul Kareem, Samir A. (2011)
Global warming and the drive to minimise greenhouse gas emissions has put the focus on how to make the most of natural energy sources. The sun is freely available almost everywhere in the world and intelligent solar tracking can help improve the exploitation and efficiency of these sustainable sources of energy. Two degree of freedom (DOF) visual-based intelligent solar tracking system using fuzzy logic control is presented in this project. The fuzzy control algorithm for solar tracking system is implemented using a webcamera as a vision sensor, two PC soundcards as output signal controller, and two DC motors as a pan-tilt driver mechanism. Two Fuzzy logic controllers are designed to control the camera panel angles of the proposed solar tracking system. The fuzzy controller input parameters (light source pixel coordinate) and output parameters (variation of duty cycle) are used to generate the optimal pulse-width- modulated (PWM) under different operating conditions to drive the motors. The motors will react accordingly when they receive signal from the sound card to ensure the camera always focuses on the centroid of the light source. The major issue addressed in this project is the reduction of the number of pulses that are sent through the soundcards to move the motors. This will significantly reduce the power consumption required to drive the camera panel to the desired location. Also using a webcamera and a sound card reduces the circuitry required when compared with conventional solar tracking systems, hence, minimizing the number of components, such as xPC target, encoder, tachometer, analog to digital converter (ADC) or digital to analog converter (DCA) and others. In short intelligent solar tracking is an obvious way to improve the efficiency of solar power plants. As the sun moves across the sky, an electric actuator system ensures that the solar panels automatically follow and maintain optimum angle in order to collect the most of the sunbeams. The proposed system in this study still has some points that need to be improved, so far, the most important limitation lies in the fact that it is not recommended to use this system for small solar panels because of high energy losses in the driving systems. The system was tested at different locations; the results of this project indicate that it is obvious that the intelligent sun tracking system is more effective in collecting solar energy compared with stationary solar panel. It can increase the voltage, current, surface temperature and power of the solar cell. The power increase gained and the efficiency over a stationary array was in excess of 67% and 40%, respectively. The data obtained by experiment such as voltage received, current, power, surface temperature and others justify the validity of the proposed controller.